Adapting Islamic Education to Society 5.0: Perspectives on Opportunities and Challenges - Lundeto, Adri; M. Aksan, Sahjad; Lundeto, Amalia Muthmainnah (Jurnal Ilmiah Iqra', 2024)
In the Society 5.0 era, which is marked by the integration of digital technology and human life, Islamic Education Institutions are faced with unique opportunities and challenges. This article reviews the opportunities and challenges of Islamic education institutions in the era of society 5.0. Then the roles and strategies carried out in overcoming this. Through a literature approach, this article presents an overview of the opportunities for Islamic educational institutions in the era of society 5.0. However, this article also identifies challenges that must be overcome by Islamic educational institutions in the era of society 5.0. By paying attention to these opportunities and challenges, Islamic Education Institutions can play a role and take strategic steps to remain existing and relevant to produce a generation that is able to compete in the era of society 5.0. The results of the first research are 5 opportunities that can be achieved by each Islamic education institution. First, providing wider access to education, second, relevant curriculum development, third, innovative learning, fourth, connection with the real world, and fifth, transformation of the role of educators. The results of the second research are 8 challenges for Islamic educational institutions in the era of society 5.0. Firstly, Islamic education must strictly adhere to educational norms and ethics that do not depart from the legal basis on which it is built, namely the Al-Qur'an and Hadith.Second, Islamic educational institutions adapt to the rise of the industrial market. Third, religious populism and identity politics, fourth, changes in roles and skills, and fifth, technology and accessibility gaps. Sixth, there are changes to the curriculum in learning, seventh, digital security and ethics. Finally, eighth, there is a change in the assessment evaluation.